Formal and Methodological Approaches to Applied Linguistics - Garzarán, Eduardo Gómez (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The goal of this Special Issue is to bring together state-of-the art articles on applied linguistics which reflect investigation carried out by researchers from different parts of the world. By bringing together papers from different perspectives, we hope to be able to gain a better understanding of the field. Hence, this Special Issue intends to address the study of language in its different dimensions and within the framework of multiple methodologies and formal accounts as used by researchers in the field. This Special Issue is dedicated to research in any area related to applied linguistics, including language acquisition and language learning; language teaching and curriculum design; language for specific purposes; psychology of language, child language and psycholinguistics; sociolinguistics; pragmatics; discourse analysis; corpus linguistics, computational linguistics and language engineering; lexicology and lexicography; and translation and interpretation.